A new genus of fossil Mymaridae (Hymenoptera) from Cretaceous amber and key to Cretaceous mymarid genera - George Poinar Jr.; John Huber (ZooKeys, 2011)
Myanmymar aresconoides gen n., sp. n. is described from one female in Burmese amber, dated as about 100 my. It is similar to Arescon on wing features but is unique among Mymaridae indistinctly segmented palpi. It is the fifth mymarid genus definitely referable to the Cretaceous period. A key to Cretaceous mymarid genera is presented and the features of Myanmymar are compared with the other Cretaceous and extant mymarid genera.